Effects of Sequential Enzymolysis and Glycosylation on the Structural Properties and Antioxidant Activity of Soybean Protein Isolate - Qing Zhang; Lin Li; Lan Chen; Shuxiang Liu; Qiang Cui; Wen Qin (MDPI AG, 2023)
The effects of limited hydrolysis following glycosylation with dextran on the structural properties and antioxidant activity of the soybean protein isolate (SPI) were investigated. Three SPI hydrolysate (SPIH) fractions, F30 (>30 kDa), F30-10 (10-30 kDa), and F10 (<10 kDa), were confirmed using gel permeation chromatography. The results demonstrated that the glycosylation of F30 was faster than that of F30-10 or F10. The enzymolysis caused the unfolding of the SPI to expose the internal hydrophobic cores, which was further promoted by the grafting of dextran, making the obtained conjugates have a loose spatial structure, strong molecular flexibility, and enhanced thermal stability. The grafting of dextran significantly enhanced the DPPH radical or •OH scavenging activity and the ferrous reducing power of the SPI or SPIH fractions with different change profiles due to their different molecular structures. The limited enzymolysis following glycosylation was proven to be a promising way to obtain SPI-based food ingredients with enhanced functionalities.